2014
DOI: 10.1542/peds.2013-3628
|View full text |Cite
|
Sign up to set email alerts
|

Youth Ice Hockey Injuries Over 16 Years at a Pediatric Trauma Center

Abstract: BACKGROUND: Youth ice hockey is an exciting sport with growing participation in the United States. Updated assessment of injury patterns is needed to determine risk factors for severe injury and develop preventive efforts. The purpose of this study was to evaluate our experience as a level 1 pediatric trauma center in Minnesota treating injured youth ice hockey players. METHODS: Children ≤18 years old who presented to our ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…A number of injury risk factors, including high velocity on the ice, unintended collisions, rapid changes in direction, and injuries from the board, puck, and sticks, lead to a high risk of a wide variety of player injuries. 24 , 27 Injuries can be categorized as a result of either a traumatic event (ie, a condition caused by an identifiable single external transfer of energy, such as a collision leading to bone fractures) or overuse (ie, there is no identifiable single external transfer of energy, but the condition is caused by multiple accumulative bouts of energy transfer, such as multiple microtraumas leading to, for example, tendon tears). 26 Depending on the surveillance methods used, the overall injury incidence in collegiate and professional men’s ice hockey currently ranges from 4.9 to 15.6 per 1000 athlete-exposures, with approximately 50 injuries per 1000 player-game hours.…”
mentioning
confidence: 99%
“…A number of injury risk factors, including high velocity on the ice, unintended collisions, rapid changes in direction, and injuries from the board, puck, and sticks, lead to a high risk of a wide variety of player injuries. 24 , 27 Injuries can be categorized as a result of either a traumatic event (ie, a condition caused by an identifiable single external transfer of energy, such as a collision leading to bone fractures) or overuse (ie, there is no identifiable single external transfer of energy, but the condition is caused by multiple accumulative bouts of energy transfer, such as multiple microtraumas leading to, for example, tendon tears). 26 Depending on the surveillance methods used, the overall injury incidence in collegiate and professional men’s ice hockey currently ranges from 4.9 to 15.6 per 1000 athlete-exposures, with approximately 50 injuries per 1000 player-game hours.…”
mentioning
confidence: 99%
“…While most previous reports of pediatric sport-related major trauma focus on a single sport, [14][15][16][17][18][19] our study examined overall patterns of major trauma related to sport and recreational activities using a provincial trauma registry. Similar to previous reports, our study found sportand recreation-related pediatric major trauma to be relatively infrequent in NS, with only 107 cases over a 13-year period (9% of all pediatric major traumas), and most traumas in males aged 11-14 years.…”
Section: Discussionmentioning
confidence: 99%
“…Ice hockey is becoming one of the most popular sports played in North America 1,2. Already being the national sport in Canada, it continues to spread in the US as 358,000 players under the age of 18 were registered with the USA Hockey in 2014–2015 3.…”
Section: Introductionmentioning
confidence: 99%
“…Youth ice hockey leagues start as young as 5 years of age. Female ice hockey participation in the US has also increased significantly, with a sevenfold increase in registrants since 1993 2,3. At the international level, hockey is now played in 77 countries recognized by the International Ice Hockey Federation 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation